Research on the Realistic Dilemmas and Innovative Practice Paths of College Career Education in the New Era - Chen, Qiujin (Education Insights, 2026)
In the context of the new era, career education in universities represents a crucial approach for fulfilling the fundamental task of fostering virtue, serving the broader national strategy of building an educational power, and effectively resolving the structural contradictions inherent in college students’ employment. Currently, there are numerous practical problems and bottlenecks in career education across Chinese universities, including lagging pedagogical concepts, rigid instructional content, monotonous delivery models, weak faculty competencies, and imperfect institutional guarantee mechanisms. Consequently, traditional employment guidance-style education is no longer suitable for the dynamic needs of modern talent cultivation and rapid social development. Based on the contemporary requirements of educational reform and the unique growth characteristics of modern college students, this article systematically analyzes the current developmental status and practical predicaments of university career education. By integrating career construction theory with the core concept of holistic education, this study explores innovative practical paths for university career education across six critical dimensions: educational concept innovation, curriculum system reconfiguration, digital and intelligent technology empowerment, practical scenario expansion, professional faculty team building, and long-term mechanism construction. Ultimately, the primary aim is to build a comprehensive, all-round, and regular career education system. This framework will significantly help college students achieve precise career positioning and sustainable lifelong career development, thereby providing robust theoretical references and practical lessons for improving the overall quality of university talent cultivation and ensuring the high-quality development of university employment initiatives.